Mechanical properties of hierarchically structured wood-cement composites - Quiroga, A. (2015)
Wood wool cement composites (WWCC) are widely used materials constituted of wood wool and Portland cement. The material presents excellent mechanical, chemical and biological properties. However, the understanding of its mechanical behavior is rather limited. In this contribution, a hierarchically structured model is presented to describe the mechanical behavior of WWCC under compressive stress. The material is modeled as 3D rigid open cellular structured material, 2D randomly oriented triple laminated material and particulated + fibrous material in the cm, mm and lm scales, respectively. The outcome of the model is a set of mathematical expressions permitting to predict the stress–strain behavior of the material in two cases: wood strands parallel and perpendicularly oriented to the stress direction. Mechanistically, the model predicts failure by buckling at the mesoscale. A statistical experimental work is included and used to validate the model.